2016
DOI: 10.4103/1450-1147.174700
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Monte Carlo method for estimation of patient-specific internal organs absorbed dose for 99m Tc-hynic-Tyr 3 -octreotide imaging

Abstract: Single-photon emission computed tomography (SPECT)-based tracers are easily available and more widely used than positron emission tomography (PET)-based tracers, and SPECT imaging still remains the most prevalent nuclear medicine imaging modality worldwide. The aim of this study is to implement an image-based Monte Carlo method for patient-specific three-dimensional (3D) absorbed dose calculation in patients after injection of 99mTc-hydrazinonicotinamide (hynic)-Tyr3-octreotide as a SPECT radiotracer. 99mTc pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…The assessment of plotted curves in Figure 3 also confirmed that the organs geometry (such as size and shape), density and the interorgan distance have the significant influence on the photon cross-irradiation SAF values. [ 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of plotted curves in Figure 3 also confirmed that the organs geometry (such as size and shape), density and the interorgan distance have the significant influence on the photon cross-irradiation SAF values. [ 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Then, the 2 dimensional areas drawn were matched and applied manually to all image series of the whole body to obtain the count pertaining to each organ. The correction related to scattering was made using the TEW method [17] and background correction was used through drawing the areas surrounding each organ and subtracting it from the count relating to that organ [6]. After background and scatter correction, the corrected counts were done based on time.…”
Section: Methodsmentioning
confidence: 99%
“…Dose distribution varies according to the choice of radiopharmaceutical and radiation specifications. Therefore, examining internal dosimetry for each patient is the great importance of this method [6].…”
Section: Introductionmentioning
confidence: 99%
“…The development of hybrid imaging technologies, such as PET/CT and SPECT/CT, increased the capability of performing patient-specific dosimetry diagnosis and therapy using radionuclides by providing spatial and temporal distribution of activity with anatomical information. [ 18 19 20 ] Furthermore, in base Monte Carlo methods, it is now possible to consider the precise geometry of the source and target organs, as well as the heterogeneities of tissues within the body for each patient, with the help of scintigraphy and anatomical images. [ 21 ] On the other hand, the patient-specific dosimetry obtained from the images of the patients, along with Monte Carlo calculations, is not only useful for optimizing the prescribed activities and increasing therapeutic efficiency but also they could also be employed for creating the minimum-effective dose and determining the dose-response relationship as a basis for predicting clinical results.…”
Section: Introductionmentioning
confidence: 99%